Blockchain Technology for Secure Digital Health Records in Pediatric Care - Santiago Luis Delgado; Mateo Santos; Carlos Mateo Ramirez (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
Blockchain technology is gaining attention in healthcare for its potential to secure and streamline digital health records. This paper explores how blockchain can enhance the security, accessibility, and interoperability of pediatric health data. By providing a decentralized and tamper-proof system, blockchain can address issues related to data privacy, patient consent, and medical history tracking in children's healthcare.